IDEOLOGICAL COMMODIFICATION OF RELIGIOUS LANGUAGE: A CRITICAL CRITIQUE OF POLITICAL HEGEMONY IN INDONESIA - Nuril Hidayati; Ahmad Musadad; Indra Tjahyadi; Sri Andayani; Alfa Zaidanil Fauzi; Ach. Mus'if (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to map the process of converting religious language from a spiritual use value into an electoral political exchange value during the 2017 Jakarta Gubernatorial Election (Pilkada DKI Jakarta). Additionally, it elucidates its ideological function in producing symbolic domination, a mechanism that remains systematically unexplained in previous literature. This study employs a qualitative design situated within the critical paradigm, adhering to the Standards for Reporting Qualitative Research (SRQR). The material object consists of a corpus of public texts from August 2016 to April 2017, selected through purposive sampling. Data analysis utilizes a three-stage progressive ideology critique technique without statistical testing, aided by deductive coding that synthesizes the theoretical frameworks of Mosco, Marx, Gramsci, and Bourdieu. The findings reveal a transfiguration of Surah Al-Mā’idah 51 into a political commodity with high exchange value. Through the Indonesian Ulema Council’s (MUI) Religious Stance document and the judicial ratification of the “religious blasphemer” label, symbolic power was constructed binarily. Operating recursively via social media algorithms and the mobilization of the 212 Action, this process successfully produced a pseudo-consciousness among voters, naturalized elite agendas into cultural hegemony, and triggered cyber polarization as well as an electoral domino effect in Banten with a narrow defeat margin of 1.9%. The primary limitation of this study is its exclusive focus on manifest texts within the public sphere, thereby excluding quantitative social media data, empirical audience reception data, or direct interviews to confirm the internal motives of the political and religious actors. The novelty of this article lies in its integrative formulation of the Ideological Commodification of Religious Language Model as a new critical diagnostic tool to dissect religious populism in post-authoritarian democracies. Future research can test the transferability of this conceptual model across other local and national electoral contests.